Perhitungan TDS Overcurrent Relay Menggunakan Adaptive Modified Firefly Algorithm - Margo Pujiantara; Rahmanditya Muhammad; Soedibyo Soedibyo (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2020)
Permanent Magnet Synchronous Machines (PMSM) have low torque in a number of specific PT. Pertamina RU V Balikpapan will be integrated with electricity sources with PT. PLN. Then there will be a change in the generator operating pattern on the system so it needs to be analyzed again. The protection system aims to isolate the interference quickly, selectively, and coordinatively so that damage to the system can be minimized and the continuity of electric power can be maintained properly. The important thing that must be considered for protection coordination, especially in overcurrent relays, is filling the TDS (Time Dial Setting) parameter. TDS regulates the relay operation time in securing a disturbance. Generally, the TDS value is determined using a manual calculation to obtain a minimum TDS value. However, to get the right TDS value in coordinating with other relays it still uses trial and error methods. In this final project, we will discuss how to calculate the time dial overcurrent relay inverse setting with the adaptive modified firefly algorithm method in the electrical system at PT. Pertamina RU V Balikpapan considers integration with PLN to obtain a minimum TDS value. The result of this final project is to obtain a minimum TDS value in some cases typical types such as the longest channel, consideration of LVCB operating time, and short channels so that it can be well-coordinated with the long lines installed on the same bus.